2017
DOI: 10.1007/s00264-017-3456-8
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and anatomic results of surgical repair of chronic rotator cuff tears at ten-year minimum follow-up

Abstract: Surgical repair of chronic rotator cuff tendon tear can produce consistent and lasting pain relief and improvement in range of motion. Re-tear of the repair was not correlated with degradation of clinical results. Best results were obtained for isolated supraspinatus tear with a complete surgical repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 34 publications
1
16
1
1
Order By: Relevance
“…However, since it was not a main aspect of our study to evaluate the previously reported conventional MRI‐based predictors, we cannot rule out that we missed predictive effects due to our small cohort size and herefrom resulting low statistical power for the expected moderate‐to‐weak effects of these parameters. The tendon retear rate within our cohort was relatively high, yet still well in the range of previous reports …”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…However, since it was not a main aspect of our study to evaluate the previously reported conventional MRI‐based predictors, we cannot rule out that we missed predictive effects due to our small cohort size and herefrom resulting low statistical power for the expected moderate‐to‐weak effects of these parameters. The tendon retear rate within our cohort was relatively high, yet still well in the range of previous reports …”
Section: Discussionsupporting
confidence: 89%
“…Goutallier et al proposed fatty muscle infiltration assessed by computed tomography as one of the first commonly applied predictors for successful tendon healing. Being adapted for the use in MRI, fatty infiltration and other MRI‐based markers such as tear size or tendon retraction represent morphologic parameters, which seem to only partially reflect functional properties and regenerative potential of the musculotendinous SSP system …”
mentioning
confidence: 99%
“…8,9 For the chronic, degenerative tear population, favorable long-term surgical outcomes have been reporteddperhaps slightly diminished when complete healing is not achieved. 10 Chronicity of the tear is a known risk factor for tear reparability. It would follow that delaying repair while the patient responds to steroid injections may be delaying the best treatment option in some instances, particularly if a trial of nonsteroidal agents and physiotherapy has already failed to improve function and reduce pain.…”
Section: See Related Article On Page 706mentioning
confidence: 99%
“…1 Despite this high incidence, RC repair does not always lead to clinically satisfactory outcomes; indeed, the failure rates of RC repair are reportedly 40-50%. [2][3][4] Therefore, RC reattachment to bone following RC repair is a challenging clinical problem. Although numerous repair techniques to reduce the re-tear rate have been reported, these did not significantly reduce the re-tear rates during long-term follow-up.…”
Section: Introductionmentioning
confidence: 99%